Rock characterization ISRM Symposium, Eurock ?92, Chester, UK, 14-17 September 1992 = Caracterisation des roches = Gesteinsansprache - Hudson, J. A. 1940- (Thomas Telford, 1992)
This book contains the papers presented at the ISRM-sponsored symposium Eurock 1992, on rock characterisation. The major themes of the symposium are: rock properties, site investigation, input to design, monitoring and back analysis, and rock engineering and the environment.